Hereditary Dehydrated Stomatocytosis due to PIEZO1 Mutation and Potential Therapeutic Target for Sickle Cell Anaemia - Afaq Ahmad Khan; Santosh G Rathod (Journal of Clinical and Diagnostic Research)
A 32-year-old female born out of a third-degree consanguineous marriage presented to the haematology clinic with generalised weakness, pallor, icterus, and pain in the left hypochondriac region. All these symptoms were for six months and progressive in nature. There was no history of similar complaints in other family members. On evaluation, the blood count showed: haemoglobin 9.9 g/L, red blood cell counts 3.37.000/mm3, white blood count of 7.1×109/L, platelets 128×109/L, Mean Corpuscular Volume (MCV) 98.3 fL, Mean Content Haemoglobin (MCH) 29.12 pg, Mean Corpuscular Haemoglobin Concentration (MCHC) 29.80 g/dL.